O-195 Disease-free survival is not impacted by fertility preservation techniques for breast cancer women. (30th June 2022) - Grynberg, M; Amsellem, N; Mayeur, A; Laup, L; Pistilli, B; Delaloge, S; Sifer, C; Sonigo, C
Abstract: Study question: Do fertility preservation (FP) strategies using ovarian stimulation or not, impact long-term disease-free survival of breast cancer (BC) patients? Summary answer: The disease-free survival of BC patients is not impacted by FP techniques whatever the timing of chemotherapy (neoadjuvant /adjuvant) and the use of ovarian stimulation.   What is known already: Fertility is often impaired in young women treated for BC. Therefore, FP has become a major issue in this population. Cryopreservation of oocytes or embryos after controlled ovarian hyperstimulation (COH) represents the most established method in this clinical situation. However, the hormonal consequences of COH protocols still raise safety concerns, often leading oncologists to contraindicate the use of this FP technique. Although alternative FP options without exogenous hormone administration may be considered, they remain suboptimal for treating the putative future infertility. Study design, size, duration: Retrospective bicentric cohort study including including 740 BC women, 18-43 years of age, referred for FP between 2013 and 2019. Participants/materials, setting, methods: Overall, 328 underwent at least one ovarian stimulation cycle (STIM group) and 412 had a technique without hormonal administration (No STIM group). Log Rank test was used to compare both groups and Cox proportional-hazard model was applied for multivariable analyses. Main results and the role of chance: Women of the No STIM group were significantly younger and present with more severe disease. Follow-up data for recurrences were available for 80.9% of the cohort and the median time to follow-up was 4.2 [2.9-5.8] vs . 5.6 [4.1-6.7] years between STIM and No STIM group ( p < 0.0001 ). According to log-rank test, the risk of recurrence did not differ between the two groups (p = 0.09) even after adjustment on age, SBR grade, triple negative status or type of planned chemotherapy. Limitations, reasons for caution: The retrospective nature of the study represents the main limitation. The median follow-up of 4.2 to 5.6 years, might be considered short to assess the long-term safety of FP techniques. The heterogeneity between oncological centers regarding the use of COH and specific protocols may lalso be a reason for caution. Wider implications of the findings: Our findings provide reassuring safety data on the use COH for FP in BC patients, whatever the timing of chemotherapy. However, further investigations with a longer follow-up are needed to definitely consider COH safe in particular in neoadjuvant situations. In addition, the benefit of letrozole supplementation during COH requires confirmation. Trial registration number: Not applicable